Scheduling with Collaborative Mobile Chargers Inter-WSNs - Jidong Zhao; Xili Dai; Xiaomin Wang (International Journal of Distributed Sensor Networks)
Mobile charge problem describes a fleet of mobile chargers delivers energy to the sensor nodes periodically in wireless sensor networks (WSNs). In it, every sensor node has an asynchronous rest working time during a charging round. We consider the asynchronous rest working time and give the lower and upper bounds of the recharging cycle by the suitable total serving rate, to give the definition of time windows for the sensor nodes. In this paper, we model this problem in 2-dimensional WSNs as a vehicle routing problem with time windows (VRPTW). For solving the problem of multiple mobile chargers with different routing paths, we propose to transform the multiple routing problems into a single routing problem, by duplicating the sink into multiple virtual sinks. To optimize the routing path, we propose a local optimization algorithm by considering the collaborative charging among the mobile chargers. Through the simulations, we compare our proposed algorithm with the H η C l u s t e r C h a r g i n g ( β ) algorithm. We demonstrate the advantages of our collaborative scheduling algorithm in this problem.